TELAAH MAQASHID AL-SYARI`AH FENOMENA CHILDFREE DALAM REALITAS KEHIDUPAN SOSIAL - Wilda Siti Hawani; Azuhria; Ilham, Muhammad (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2023)
Couples who choose not to have children in their marriage are called childfree. Many married couples choose not to have children. It is indeed impossible to make a quick decision not to have children. Couples decide not to have children due to many factors. The opinion that marriage should not result in children has recently become widespread. This is sure to reap a lot of protes in society because it goes against cultural, religious and Indonesian societal norm. The reason behind this is that it is not true. This research method is qualitative, and a literature survey is used, which comes from articles and journals. Basically, not having children is allowed because of the basic laws of marriage too. On the other hand, not having children is not permitted because it is against maqashid al-syari`ah. There is no right or wrong, but the decision to however, couples must make a joint decision not to have children.